Ocena wydzielania łez u pacjentów po chirurgii refrakcyjnej - Mrukwa-Kominek, Ewa; Stala, Paweł; Gierek-Ciaciura, Stanisława; Lange, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: One of the complications of the corneal refractive surgery is a transient disturbance in tears secretion, which can lead to the dry eye syndrome. The aim of the study was to evaluate the tears secretion in patients after PRK, LASEK and LASIK surgery for myopia. Material and methods: We examined 115 eyes of 69 patients (46 woman and 23 men), mean age 30.82, with myopia and myopic astigmatism, treated with three different refractive procedures. The patients included in this study were divided into three groups: Group I: 35 eyes of 22 patients (15 woman and 7 men) treated with PRK. The mean spherical equivalent of the refractive error was -4.18 dioptres (from -8.75 to -2.0). Group II: 41 eyes of 23 patients (13 woman and 10 men) treated with LASEK. The mean spherical equivalent of the refractive error was -5.73 dioptres (from -12.0 to -2.75). Group III: 39 eyes of 24 patients (18 woman and 6 men) treated with LASIK. The mean spherical equivalent of the refractive error was -7.49 dioptres (from -10.75 to -3.75). In this study the amount of tears secreted was analyzed on the base of Schirmer I test, performed before and after surgery. Test was always performed in the same room, in the morning hours (before noon), with constant temperature and air humidity values. Results: In the PRK group the mean value of Schirmer I test was 20.91 mm before surgery. 14 days after surgery the mean value decreased to 14.09 mm, 1 month after surgery to 11.66 mm. Then increase in tears secretion was observed: 2 months after surgery the mean value of Schirmer I test was 13.94 mm, 3 months after surgery 15.23 mm, and 6 months after surgery 17.4 mm. In the LASEK group the mean value of Schirmer I test was 20.39 mm before surgery. 14 days after surgery the mean value decreased to 15.78 mm, 1 month after surgery to 13.05 mm. Two months after surgery the mean value of Schirmer I test was 15.24 mm, 3 months after surgery 16.17 mm, and 6 months after surgery 18.15 mm. In the LASIK group the mean value of Schirmer I test was 20.72 mm before surgery. 14 days after surgery the mean value decreased to 12.97 mm, 1 month after surgery to 5 mm. 2 months after surgery mean value of Schirmer I test was 12.79 mm, 3 months after surgery 15.05 mm, and 6 months after surgery 17.82 mm. Conclusions: Corneal refractive surgery causes transient reduction of tears secretion, especially during the first three postoperative months. The tears secretion was reduced most significantly in the LASIK group. In patients treated with PRK and LASEK tears secretion during the postoperative period was comparable with slightly better secretion in the LASEK patients.